MOTIVATIONAL STRATEGIES APPLIED IN THE FIRST GRADE OF PRIMARY SCHOOL - Yousevin Yousevin; Josefa J. Mardijono (Kata Kita: Journal of Language, Literature, and Teaching, 2015)
This study was conducted in order to find out the motivational strategies applied by an English teacher who was perceived successful in motivating students in learning English in a primary school in Surabaya. It was focused on the motivational strategies related to appropriate teacher behaviors and a good relationship with the students; a pleasant and supportive classroom atmosphere; and a cohesive learner group with appropriate group norms in the first grade of primary school. Using qualitative approach, this study is based on Dörnyei’s (2001) theory on motivational strategies. The data were collected from verbal and non-verbal interaction between the teacher and students in the classroom, in two meetings within two weeks. The duration of the class was 70 minutes for each meeting. The findings showed that the English teacher applied motivational strategies related to the first and second motivational components. Mostly, the teacher applied motivational strategies related to the first motivational component. However, the teacher did not apply any motivational strategies related to the third motivational component, since there was no activity related to making groups in the classroom. It can be said that by applying all those motivational strategies, the students could be motivated in learning English and be more active in following the lesson in the classroom